Electronic word of mouth in tourism and hospitality consumer behaviour: state of the art. Issue 4 (12th February 2020) - Pourfakhimi, Shahab; Duncan, Tara; Coetzee, Willem J.L.
Abstract : Purpose: Despite its volume, the academic research on the impact of electronic word of mouth (eWOM) on tourism and hospitality consumer behaviour is fragmented and largely limited to investigating a small scope of its impact. The purpose of this paper is to bridge this gap by synthesising the existing literature, providing a conceptual framework for the various dimensions of this impact. Design/methodology/approach: This paper is based on the meta-synthesis and a critical conceptual analysis of relevant academic literature identified using a keyword search of papers via the Web of Science and Scopus databases, followed by a snowballing process comprising tracking the citations to the resources referred to in the identified papers. Findings: This conceptual analysis illustrates how the full spectrum of the impact of eWOM on tourist behaviour spans well beyond the limited scope traditionally focussed on by tourism and hospitality researchers. This scope, encompassing multiple cognitive, normative and affective dimensions, is illustrated in an evidence-based conceptual framework proposed in this paper, providing a systematic tool to identify the less-studied aspects of this important phenomenon. Originality/value: This paper synthesises the large and fragmented body of literature on eWOM and proposes a novel conceptual framework, illustrating the vast scope of the various cognitive, affective and normative mechanisms through which eWOM affects consumers' choice of tourism and hospitality products. Furthermore, this paper provides a synthesis of the state-of-the-art of research in this field, highlights the existing gaps and provides researchers with a systematic tool to identify pathways towards breaking the status-quo in progressing beyond the current boundaries of academic research in this field. Abstract : 游客感知对清真旅游目的地的影响：结构模型分析 目的: 尽管有大量研究, 但有关网络口碑eWOM对旅游业和酒店业消费者行为的影响的学术研究仍是零散的, 并且在很大程度上只限于调查其影响的一小部分。本文的目的是通过综合现有文献来弥合这种差距, 为这种影响的各个方面提供概念框架。 设计/方法/方法: 本文基于元合成法和对相关学术文献的关键性, 概念性分析。这些文献是通过Web of Science和Scopus数据库对文章进行关键字搜索而确定的。随后是滚雪球式搜索过程, 该过程包括跟踪对已识别文章中引用的资源的引用。 结果: 这项概念分析阐述了eWOM对游客行为的影响范围如何远远超出了旅游和酒店业研究人员传统上关注的有限范围。这一范围是基于有理论依据的的概念框架提出的, 并涵盖多个认知, 规范和情感的维度。此范围为识别这一重要且缺乏研究的现象提供了系统的工具。 创意/价值: 本文综合了有关eWOM的大量零散文献, 并提出了一个新颖的概念框架, 阐明了eWOM影响消费者选择旅游和酒店产品的各种认知, 情感和规范机制的范围。此外, 本文提供了该领域最新的研究综述, 突出了现有的差距, 并为研究人员提供了系统的识别打破现状的途径, 以超越当前学术界在这个领域的研究局限。 关键词: 关键字 电子口碑, eWOM, WOM, 酒店, 旅游, 口碑 文章类型: 研究论文 Abstract : El Boca a Boca Electrónico en el Comportamiento del Consumidor Turístico y Hotelero: Estado del Arte Objetivo: A pesar del gran volumen de investigación académica sobre el impacto de eWOM en el comportamiento del consumidor turístico y hotelero, esta se encuentra fragmentada y en gran medida se limita a investigar un pequeño alcance de su impacto. El propósito de este artículo, es cerrar esta brecha sintetizando la literatura existente y proporcionando un marco conceptual para las diversas dimensiones de este impacto. Diseño/metodología/enfoque: Este documento se basa en un análisis metasíntesis crítico y conceptual de la literatura relevante académica identificada, mediante una búsqueda de artículos por palabras claves a través de las bases de datos de Web of Science y Scopus, seguido de un proceso de "bola de nieve" que comprende el seguimiento de las citas de los recursos mencionados en los artículos identificados. Resultados: Este análisis conceptual, ilustra cómo el espectro total del impacto de eWOM en el comportamiento turístico se extiende mucho más allá del limitado alcance que tradicionalmente han realizado investigadores del turismo y hoteles. Este nuevo alcance, que abarca múltiples dimensiones cognitivas, normativas y afectivas, se ilustra en un marco conceptual basado en la evidencia propuesta en este documento, que proporciona una herramienta sistemática para identificar los aspectos menos estudiados de este importante fenómeno. Originalidad/valor: Este documento sintetiza la gran cantidad de literatura fragmentada sobre eWOM y propone un marco conceptual novedoso, que ilustra el amplio alcance de los diversos mecanismos cognitivos, afectivos y normativos a través de los cuales eWOM afecta la elección de los consumidores de productos turísticos y hoteleros. Además, este documento proporciona una síntesis del estado de la investigación en este campo, destaca las brechas existentes y brinda a los investigadores una herramienta sistemática para identificar vías para romper el statu quo en el progreso más allá de los límites académicos actuales en este campo. Palabras clave: Boca a boca electrónica, eWOM, WOM, Industria hoteleram, Turismo, Boca a boca Tipo de papel: – Trabajo de investigación